Tris(trichlorosilyl)tetrelide Anions and a Comparative Study of Their Donor Qualities. Issue 11 (25th January 2019) - Teichmann, Julian; Kunkel, Chantal; Georg, Isabelle; Moxter, Maximilian; Santowski, Tobias; Bolte, Michael; Lerner, Hans‐Wolfram; Bade, Stefan; Wagner, Matthias
Abstract: Trichlorosilylated tetrelides [(Cl3 Si)3 E] − have been prepared by adding 1 equiv of a soluble Cl − salt to (Cl3 Si)4 Si (E=Si) or 4 Si2 Cl6 /GeCl4 (E=Ge). To assess their donor qualities, the anions [(Cl3 Si)3 E] − (E=C, Si, Ge) have been treated with BCl3, AlCl3, and GaCl3 . Both BCl3 and GaCl3 give 1:1 adducts with the anionic centers. AlCl3 leads to Cl − abstraction from [(Cl3 Si)3 E] − with formation of (Cl3 Si)4 E (E=Si or Ge). (Cl3 Si)4 Ge is cleanly converted to the perhydrogenated (H3 Si)4 Ge by use of Li[AlH4 ]. Another case of Cl − abstraction was observed for [(Cl3 Si)3 Ge⋅ GaCl3 ] −, which reacts with GaCl3 to afford the neutral dimer [(Cl3 Si)3 Ge−GaCl2 ]2 . Abstract : Cornerstone added : The trichlorosilylated germanide [(Cl3 Si)3 Ge] − is readily accessible from GeCl4 and Si2 Cl6 /Cl − . All tetrelides [(Cl3 Si)3 E] − (E=C, Si, Ge) were found surprisingly nucleophilic and form adducts with BCl3 and GaCl3 . The unique (Cl3 Si)4 Ge was obtained through an AlCl3 ‐induced rearrangement of [(Cl3 Si)3 Ge] − .